Biodegradable film with high light transmittance and efficient ultraviolet shielding function as well as preparation method and application of biodegradable film

By using lignin-tannin composite nanoparticles in biodegradable films, the problem of volatility of ultraviolet absorbers in existing anti-ultraviolet aging films is solved, high transparency and efficient ultraviolet shielding effect are achieved, and crops in agricultural greenhouses are improved Growth and yield.

CN119144107AActive Publication Date: 2024-12-17SICHUAN UNIV

Patent Information

Application Number
CN202411241275.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-17
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The ultraviolet absorbers used in existing anti-UV aging biodegradable films have small molecular weight, are volatile and unstable, making them difficult to be suitable for degraded materials, resulting in poor use in agricultural greenhouses, affecting crop growth and yield.

Method used

Using lignin-tannin composite nanoparticles, a high-transparent and efficient ultraviolet shielding biodegradable film was prepared by solution casting. The self-assembly characteristics of lignin and tannin were used to generate regular composite nanoparticles, which enhanced the ultraviolet shielding performance and reduced the The film color achieves high transparency and efficient ultraviolet shielding effect under low addition amount.

Benefits of technology

It significantly improves the ultraviolet shielding performance and transparency of the film, extends the service life of the film, increases the temperature and yield of the crop growth environment, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144107A_ABST
    Figure CN119144107A_ABST
Patent Text Reader

Abstract

The invention discloses a biodegradable film with high light transmittance and efficient ultraviolet shielding as well as a preparation method and application of the biodegradable film. The invention provides a biodegradable film with high light transmittance and efficient ultraviolet shielding. The biodegradable film comprises a bio-based degradable film and lignin-tannin composite nanoparticles located in the bio-based degradable film. According to the biodegradable film with high light transmittance and efficient ultraviolet shielding, the structural characteristics of the lignin and the tannin are fully utilized, and the ultraviolet shielding performance can be remarkably enhanced through composite particles generated through self-assembly of the lignin and the tannin, pi-pi accumulation of benzene rings in the lignin structure and rich phenolic hydroxyl groups in the tannin structure. In addition, the color of tannin is lighter than that of lignin, and the film color can be obviously reduced. Therefore, the biodegradable film with high transparency and efficient ultraviolet shielding effect can be prepared under the condition of low additive amount.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-ultraviolet materials, and in particular to a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet rays, and a preparation method and application thereof. Background Art

[0002] The quality of light and the growth environment are very important for the growth of plants. The agricultural films used in greenhouses have superior performance in terms of light transmittance, heat preservation, tensile strength and aging resistance, which are of great significance to the growth, production increase and income increase of greenhouse plants.

[0003] Biodegradable film with high light transmittance and high efficiency in shielding UV rays is a functional agricultural film that reduces the damage of UV rays to film materials by introducing UV absorbers, thereby extending the service life of the film. The UV absorbers in the anti-UV aging biodegradable film can absorb UV rays and release them as harmless energy. The heat released in this process can increase a certain temperature for crop growth and development, which is conducive to accelerating the growth process of crops. In addition, the addition of UV absorbers can alleviate the degradation of biodegradable films and extend the covering period of biodegradable film materials, which will help increase crop yields. Therefore, the use of anti-UV aging biodegradable films is of great significance to the development of agricultural production.

[0004] At present, the commonly used organic UV absorbers mainly include benzophenone, benzotriazole, triazine and salicylate. The main problems of these UV absorbers are small molecular weight, volatility and migration, and they are mostly used in traditional plastics. Therefore, UV absorbers suitable for degradable materials with stable effects and biodegradable films with UV resistance are urgently needed in the market. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet rays, as well as a preparation method and application thereof.

[0006] The present invention solves the technical problem by adopting the following technical solutions.

[0007] The invention provides a highly light-transmitting and highly efficient ultraviolet shielding biodegradable film, comprising: a bio-based degradable film and lignin-tannin composite nanoparticles located in the bio-based degradable film.

[0008] The present invention also provides a method for preparing the above-mentioned biodegradable film with high light transmittance and high efficiency in shielding ultraviolet rays, which comprises: preparing the biodegradable film with high light transmittance and high efficiency in shielding ultraviolet rays by a solution casting method.

[0009] The present invention also provides an application of the above-mentioned biodegradable film with high light transmittance and high efficiency in shielding ultraviolet rays in agricultural greenhouse films.

[0010] The present invention has the following beneficial effects:

[0011] The present invention provides a highly light-transmitting and highly efficient ultraviolet shielding biodegradable film, and a preparation method and application thereof. The highly light-transmitting and highly efficient ultraviolet shielding biodegradable film provided by the present invention comprises: a bio-based degradable film and lignin-tannin composite nanoparticles located in the bio-based degradable film. The highly light-transmitting and highly efficient ultraviolet shielding biodegradable film provided by the present invention makes full use of the structural characteristics of lignin and tannin, and generates regular lignin-tannin composite nanoparticles by self-assembly of lignin and tannin, thereby improving the dispersibility of lignin-tannin composite nanoparticles in the bio-based degradable film. At the same time, the π-π stacking of benzene rings in the lignin structure and the abundant phenolic hydroxyl groups in the tannin structure can significantly enhance the ultraviolet shielding performance. Tannin is lighter in color than lignin, and can significantly reduce the color of the film. Thus, a film material having both high transparency and high-efficiency ultraviolet shielding effect can be prepared at a low addition amount. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0013] Figure 1 The SEM and particle size distribution of lignin nanoparticles and lignin-bayberry tannin nanoparticles;

[0014] Figure 2 is the distribution of lignin nanoparticles and lignin-tannin composite nanoparticles in PVA film;

[0015] Figure 3 The UV-visible transmittance curves and UV protection index values ​​of composite films with different compositions are shown;

[0016] Figure 4 The photodegradation performance of four different photosensitive pesticides under the cover of composite film. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0018] The purpose of the present invention is to provide a preparation method of a high-efficiency ultraviolet shielding biodegradable film prepared from lignin-tannin composite nanoparticles. The method uses renewable biomass resources with abundant reserves as raw materials, realizes the high-value utilization of lignin and tannin, and promotes the utilization of all components of biomass resources. The prepared high-light-transmittance and high-efficiency ultraviolet shielding biodegradable film has both high transparency and high-efficiency ultraviolet shielding performance at a low addition amount, and the preparation method is simple and the production cost is low.

[0019] The following is a detailed description of a highly light-transmitting and highly efficient UV-shielding biodegradable film provided in an embodiment of the present invention, as well as a preparation method and application thereof.

[0020] In a first aspect, an embodiment of the present invention provides a biodegradable film with high light transmittance and high UV shielding efficiency, comprising a bio-based degradable film and lignin-tannin composite nanoparticles located in the bio-based degradable film.

[0021] The embodiment of the present invention provides a highly transparent and efficient UV shielding biodegradable film, and the bio-based degradable film contains lignin-tannin composite nanoparticles. Lignin is a natural aromatic polymer formed by connecting phenylpropane units through CC bonds and CO bonds. It is abundant in nature and its content is second only to cellulose. Based on the large number of benzene rings and hydrophilic groups in the lignin structure, the lignin oligomers dissolved in the organic solvent, in the process of gradually adding anti-solvent (water), the benzene rings are accumulated through π-π interactions to form a hydrophobic core, and at the same time, a hydrophilic shell mainly composed of hydrophilic groups such as phenolic hydroxyl, alcoholic hydroxyl, and carboxyl is formed, thereby generating lignin nanoparticles dispersed in the water solvent. Lignin nanoparticles have excellent UV shielding properties, and adding them to the film material can significantly improve the UV shielding properties of the film material. However, while the excessive addition amount brings high-efficiency UV shielding properties, it will cause the film color to deepen, and the compatibility with the film material will also deteriorate. Tannin, a natural polyphenol compound, has a huge reserve in nature, contains abundant phenolic hydroxyl groups in the structure, and exhibits excellent UV resistance. However, due to its strong hydrophilicity, tannin's self-assembly performance is poor.

[0022] Thus, the highly transparent and highly efficient UV shielding biodegradable film provided by the embodiment of the present invention is a composite particle generated by self-assembly of lignin and tannin, and the π-π stacking of benzene rings in the lignin structure and the abundant phenolic hydroxyl groups in the tannin structure can significantly enhance the UV shielding performance. In addition, the color of tannin is lighter than that of lignin, which can significantly reduce the color of the film. Thus, a film material with both high transparency and efficient UV shielding effect can be prepared at a low addition amount.

[0023] In an optional embodiment, the amount of lignin-tannin composite nanoparticles added to the bio-based degradable film is 1%-10%, preferably 3%-5%.

[0024] In an optional embodiment, the mass ratio of lignin to tannin is (9:1)-(1:9), more preferably (6:4)-(4:6);

[0025] Preferably, the tannin includes at least one of bayberry tannin, larch tannin, tangerine tannin, acacia mangium tannin, and black wattle bark tannin;

[0026] Preferably, the lignin includes at least one of organically soluble lignin, alkali lignin, enzymatically hydrolyzed lignin, and sodium lignin sulfonate.

[0027] In an optional embodiment, the bio-based degradable film is prepared by using one or more of polyvinyl alcohol, polylactic acid, chitosan, and gelatin.

[0028] In a second aspect, an embodiment of the present invention further provides a method for preparing the above-mentioned biodegradable film with high light transmittance and high efficiency in shielding ultraviolet rays, which comprises: preparing the biodegradable film with high light transmittance and high efficiency in shielding ultraviolet rays by a solution casting method.

[0029] In an optional embodiment, the preparation of lignin-tannin composite nanoparticles includes: adding lignin and tannin to a mixed solvent of acetone and water, stirring and dissolving to obtain a mixed solution; placing the mixed solution in an ultrasonic environment, adding distilled water thereto, and continuing to sonicate after the addition is completed to allow lignin and tannin to fully self-assemble, thereby obtaining lignin-tannin composite nanoparticles;

[0030] Preferably, the mass ratio of lignin to tannin is (9:1)-(1:9), more preferably (6:4)-(4:6);

[0031] Preferably, the concentration of the lignin-tannin solution is 1 mg / mL-50 mg / mL, more preferably 5 mg / mL-10 mg / mL;

[0032] Preferably, the distilled water droplet acceleration is 1 mL / min-20 mL / min, more preferably 5 mL / min-10 mL / min;

[0033] Preferably, the method further comprises: after the lignin and tannin are fully self-assembled, centrifuging the crude product, removing the supernatant, continuing to centrifuge and wash, and then freeze-drying to obtain lignin-tannin composite nanoparticles.

[0034] In an optional embodiment, the preparation of lignin includes: extracting lignin from the first biomass raw material by a solvothermal method, and obtaining organically dissolved lignin by dichloromethane extraction;

[0035] Preferably, the temperature for extracting lignin from the first biomass raw material by solvothermal method is 180°C-240°C, more preferably 200°C-220°C;

[0036] Preferably, the solid-liquid ratio of the lignin in the first biomass raw material extracted by the solvothermal method is (1:100)-(10:100), more preferably (3:100)-(6:100);

[0037] Preferably, the ratio of acetone to water in extracting lignin from the first biomass raw material by solvothermal method is (1:9)-(9:1), more preferably (4:6)-(9:1);

[0038] Preferably, the extraction time of lignin in the first biomass raw material by the solvothermal method is 0.5h-3h, more preferably 1h-2h;

[0039] Preferably, the first biomass raw material includes at least one of pine wood powder and red cedar powder;

[0040] Preferably, the first biomass raw material is placed in a mixed solvent of acetone and water and kept at 180°C-240°C for a period of time, and then the obtained extract is extracted with dichloromethane, and the extracted organic phase is subjected to rotary evaporation to remove dichloromethane and acetone, and then dried to obtain organic dissolved lignin.

[0041] In an optional embodiment, the preparation of tannin includes: extracting tannin from the second biomass raw material by a solvothermal method, and obtaining water-insoluble tannin by distilled water precipitation;

[0042] Preferably, the temperature for extracting tannin from the second biomass raw material by solvothermal method is 40°C-80°C, more preferably 50°C-60°C;

[0043] Preferably, the temperature for extracting tannin from the second biomass raw material by solvothermal method is 40°C-80°C, more preferably 50°C-60°C;

[0044] Preferably, the solid-liquid ratio of the tannin extracted from the second biomass raw material by the solvothermal method is (1:100)-(20:100), more preferably (5:100)-(15:100);

[0045] Preferably, the ratio of acetone to water for extracting tannins from the second biomass raw material by solvothermal method is (1:9)-(9:1), more preferably (4:6)-(9:1);

[0046] Preferably, the second biomass raw material includes at least one of waxberry, larch, citrus aurantium, acacia mangium, and black wattle bark;

[0047] Preferably, the second biomass raw material is placed in a mixed solvent of acetone and water, kept at 40°C-80°C for a period of time, and then the obtained extract is subjected to rotary evaporation to remove acetone, centrifuged and washed with water, and then dried to obtain water-insoluble tannins.

[0048] The embodiment of the present invention provides a highly light-transmitting and highly efficient UV-shielding biodegradable film, wherein the bio-based degradable film contains lignin-tannin composite nanoparticles. In the preparation process of the lignin-tannin composite nanoparticles, the lignin extracted from the first biomass raw material is extracted with dichloromethane to obtain organic soluble lignin, and the tannin extracted from the second biomass raw material is precipitated with distilled water to obtain water-insoluble tannin. After the lignin and tannin are purified, water-soluble components (such as small molecule sugars, carboxylic acids, proteins, water-soluble tannin monomers, etc.) can be avoided to interfere with self-assembly, and the ultrasonic-assisted treatment is promoted to obtain regular lignin-tannin composite nanoparticles, and the nano-size effect improves their dispersibility in the bio-based degradable film. It can also be seen from the test results that the lignin-tannin composite nanoparticles prepared above are uniformly dispersed in the bio-based degradable film, so that the prepared composite film can be prepared at a low addition amount. Biodegradable film with both high transparency and high-efficiency UV shielding effect.

[0049] In an optional embodiment, the preparation of a highly light-transmitting and highly efficient UV-shielding biodegradable film comprises: mixing lignin-tannin composite nanoparticles with a biodegradable polymer solution, and then forming a film using a solution casting method to obtain a highly light-transmitting and highly efficient UV-shielding biodegradable film;

[0050] Preferably, the addition amount of lignin-tannin composite nanoparticles is 1%-10%, more preferably 3%-5%;

[0051] Preferably, the mass concentration of the biodegradable polymer solution is 3% and the dissolution temperature is 90°C;

[0052] Preferably, the biodegradable polymer includes one or more of polyvinyl alcohol, polylactic acid, chitosan and gelatin.

[0053] In a third aspect, an embodiment of the present invention further provides an application of the above-mentioned biodegradable film with high light transmittance and high efficiency in shielding ultraviolet rays in agricultural greenhouse films.

[0054] The present invention will be further described below in conjunction with the embodiments.

[0055] The polyvinyl alcohol used in the following examples and comparative examples is abbreviated as PVA, lignin is abbreviated as L, and tannin is abbreviated as T.

[0056] Example 1

[0057] A method for preparing a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet light, comprising the following steps:

[0058] ① Lignin and tannin extraction: Lignin and tannin were extracted separately by solvothermal method. The extraction conditions of lignin were as follows: 18 g pine powder, 300 mL mixed solvent (210 mL acetone and 90 mL secondary water), extraction temperature 220°C, time 2 h, followed by extraction with dichloromethane, collecting the organic phase, removing the organic solvent by rotary evaporation, and drying in an oven at 105°C to obtain the organic-soluble lignin, with a yield of 26.5%; the extraction conditions of tannin were as follows: 50 g bayberry bark powder, 500 mL mixed solvent (350 mL acetone and 150 mL secondary water), extraction temperature 50°C, time 3 h, followed by removal of the organic solvent by rotary evaporation, and water-insoluble bayberry tannin was obtained after centrifugal washing, with a yield of 9.0%.

[0059] ② Preparation of lignin-tannin composite nanoparticles: Add 200 mg of lignin and 200 mg of bayberry tannin to 40 mL of mixed solvent (28 mL of acetone and 12 mL of distilled water), stir with a glass rod to dissolve them completely, and place them in an ultrasonic environment. The ultrasonic conditions are: 30°C, 45 kHz, 100%. 240 mL of distilled water is added dropwise at a flow rate of 10 mL / min through a constant flow pump. After the addition is completed, continue to ultrasonicate for 30 minutes to allow lignin and tannin to fully self-assemble. Centrifuge, remove the supernatant, continue to centrifuge and wash with water 3 times, and freeze-dry to obtain lignin-bayberry tannin composite nanoparticles with a yield of 47.8%.

[0060] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃, for 2h, dissolve PVA completely, and obtain PVA solution; add the above-prepared lignin-tannin composite nanoparticles to the PVA solution at an addition amount of 3%, stir magnetically, at 60℃, for 0.5h, mix PVA and lignin-tannin composite nanoparticles thoroughly, pour into 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould, obtain composite film, store in a desiccator, the composition of composite film is PVA-LT. The composite film is tested by UV-visible spectrophotometer equipped with integrating sphere, and the transmittance of visible light is 62%, and the transmittance of ultraviolet light is 1.5%.

[0061] Example 2

[0062] A method for preparing a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet light, comprising the following steps:

[0063] ① Lignin and tannin extraction: Lignin and tannin were extracted separately by solvothermal method. The extraction conditions of lignin were as follows: 24 g pine powder, 300 mL mixed solvent (210 mL acetone and 90 mL secondary water), extraction temperature 220°C, time 2 h, followed by extraction with dichloromethane, collecting the organic phase, removing the organic solvent by rotary evaporation, and drying in an oven at 105°C to obtain the organic-soluble lignin, with a yield of 24.9%; the extraction conditions of tannin were as follows: 50 g larch bark powder, 500 mL mixed solvent (350 mL acetone and 150 mL secondary water), extraction temperature 60°C, time 3 h, followed by removal of the organic solvent by rotary evaporation, and water-insoluble larch tannin was obtained after centrifugal washing, with a yield of 6.3%.

[0064] ② Preparation of lignin-tannin composite nanoparticles: Add 40 mg of lignin and 360 mg of larch tannin to 80 mL of mixed solvent (56 mL of acetone and 24 mL of distilled water), stir with a glass rod to dissolve them completely, and place them in an ultrasonic environment. The ultrasonic conditions are: 30°C, 45 kHz, 100%. 480 mL of distilled water is added dropwise at a flow rate of 5 mL / min through a constant flow pump. After the addition is completed, continue to ultrasonicate for 30 minutes to allow lignin and tannin to fully self-assemble. Centrifuge, remove the supernatant, continue to centrifuge and wash with water 3 times, and freeze-dry to obtain lignin-larch tannin composite nanoparticles with a yield of 30.5%.

[0065] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃ for 2h, dissolve PVA completely, and obtain PVA solution; add the prepared lignin-tannin composite nanoparticles to PVA at 10%, stir magnetically, at 60℃ for 0.5h, mix PVA and lignin-tannin composite nanoparticles thoroughly, pour into 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould, obtain composite film, store in desiccator, the composition of composite film is PVA-LT. The composite film is tested by UV-visible spectrophotometer equipped with integrating sphere, and the transmittance of visible light is 29%, and the transmittance of ultraviolet light is 13%.

[0066] Example 3

[0067] A method for preparing a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet light, comprising the following steps:

[0068] ① Lignin and tannin extraction: Lignin and tannin were extracted separately by solvothermal method. The extraction conditions of lignin were as follows: 18g pine powder, 300mL mixed solvent (210mL acetone and 90mL secondary water), extraction temperature 200℃, time 2h, followed by extraction with dichloromethane, collecting the organic phase, removing the organic solvent by rotary evaporation, and drying in an oven at 105℃ to obtain the organic-soluble lignin, with a yield of 24.3%; the extraction conditions of tannin were as follows: 50g tangerine bark powder, 500mL mixed solvent (350mL acetone and 150mL secondary water), extraction temperature 80℃, time 3h, followed by removal of the organic solvent by rotary evaporation, and water-insoluble tangerine tannin was obtained after centrifugal washing, with a yield of 1.5%.

[0069] ② Preparation of lignin-tannin composite nanoparticles: Add 380 mg of lignin and 20 mg of tangerine tannin to 40 mL of mixed solvent (28 mL of acetone and 12 mL of distilled water), stir with a glass rod to dissolve them completely, and place them in an ultrasonic environment. The ultrasonic conditions are: 30°C, 45 kHz, 100%. Add 240 mL of distilled water at a flow rate of 2 mL / min through a constant flow pump. After the addition is completed, continue to ultrasonicate for 30 minutes to allow lignin and tannin to fully self-assemble. Centrifuge, remove the supernatant, continue to centrifuge and wash with water 3 times, and freeze-dry to obtain lignin-tangerine tannin composite nanoparticles with a yield of 57.1%.

[0070] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃, and last for 2h to completely dissolve PVA to obtain PVA solution; add the above-prepared lignin-tannin composite nanoparticles to the PVA solution at an addition amount of 6%, stir magnetically, and hold at 60℃ for 0.5h to fully mix PVA and lignin-tannin composite nanoparticles, and pour into a 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould to obtain a composite film, and store it in a desiccator. The composition of the composite film is PVA-LT. The composite film was tested by a UV-visible spectrophotometer equipped with an integrating sphere, and the transmittance of visible light was 23%, and the transmittance of ultraviolet light was 2%.

[0071] Example 4

[0072] A method for preparing a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet light, comprising the following steps:

[0073] ① Lignin and tannin extraction: Lignin and tannin were extracted separately by solvothermal method. The extraction conditions of lignin were as follows: 30g pine powder, 300mL mixed solvent (210mL acetone and 90mL secondary water), extraction temperature 240℃, time 2h, followed by extraction with dichloromethane, collecting the organic phase, removing the organic solvent by rotary evaporation, and drying in an oven at 105℃ to obtain the organic-soluble lignin, with a yield of 22.3%; the extraction conditions of tannin were as follows: 50g bayberry bark powder, 500mL mixed solvent (350mL acetone and 150mL secondary water), extraction temperature 50℃, time 3h, followed by removing the organic solvent by rotary evaporation, and obtaining water-insoluble bayberry tannin after centrifugal washing, with a yield of 9.0%.

[0074] ② Preparation of lignin-tannin composite nanoparticles: Add 20 mg of lignin and 380 mg of bayberry tannin to 8 mL of mixed solvent (5.6 mL of acetone and 2.4 mL of distilled water), stir with a glass rod to dissolve them completely, and place them in an ultrasonic environment. The ultrasonic conditions are: 30°C, 45 kHz, 100%. 48 mL of distilled water is added dropwise at a flow rate of 1 mL / min through a constant flow pump. After the addition is completed, continue to ultrasonicate for 30 minutes to allow lignin and tannin to fully self-assemble. Centrifuge, remove the supernatant, continue to centrifuge and wash with water 3 times, and freeze-dry to obtain lignin-bayberry tannin composite nanoparticles with a yield of 40.2%.

[0075] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃, for 2h, dissolve PVA completely, and obtain PVA solution; add 8% of the lignin-tannin composite nanoparticles prepared above to the PVA solution, stir magnetically, at 60℃, for 0.5h, mix PVA and lignin-tannin composite nanoparticles thoroughly, pour into 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould, obtain composite film, store in a desiccator, the composition of composite film is PVA-LT. The composite film is tested by UV-visible spectrophotometer equipped with integrating sphere, and the transmittance of visible light is 36%, and the transmittance of ultraviolet light is 15%.

[0076] Example 5

[0077] A method for preparing a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet light, comprising the following steps:

[0078] ① Lignin and tannin extraction: Lignin and tannin were extracted separately by solvothermal method. The extraction conditions of lignin were as follows: 18 g pine wood powder, 300 mL mixed solvent (210 mL acetone and 90 mL secondary water), extraction temperature 180°C, time 2 h, followed by extraction with dichloromethane, collecting the organic phase, removing the organic solvent by rotary evaporation, and drying in an oven at 105°C to obtain the organic-soluble lignin, with a yield of 20.1%; the extraction conditions of tannin were as follows: 50 g bayberry bark powder, 500 mL mixed solvent (350 mL acetone and 150 mL secondary water), extraction temperature 40°C, time 3 h, followed by removal of the organic solvent by rotary evaporation, and water-insoluble bayberry tannin was obtained after centrifugal washing, with a yield of 7.2%.

[0079] ② Preparation of lignin-tannin composite nanoparticles: Add 360 mg of lignin and 40 mg of bayberry tannin to 200 mL of mixed solvent (140 mL of acetone and 60 mL of distilled water), stir with a glass rod to dissolve them completely, and place them in an ultrasonic environment. The ultrasonic conditions are: 30°C, 45 kHz, 100%. 1200 mL of distilled water is added dropwise at a flow rate of 20 mL / min through a constant flow pump. After the addition is completed, continue to ultrasonicate for 30 minutes to allow lignin and tannin to fully self-assemble. Centrifuge, remove the supernatant, continue to centrifuge and wash with water 3 times, and freeze-dry to obtain lignin-bayberry tannin composite nanoparticles with a yield of 55.6%.

[0080] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃ for 2h, dissolve PVA completely to obtain PVA solution; add 1% of the lignin-tannin composite nanoparticles prepared above to the PVA solution, stir magnetically, at 60℃ for 0.5h, mix PVA and lignin-tannin composite nanoparticles thoroughly, pour into 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould to obtain composite film, store in a desiccator, the composition of the composite film is PVA-LT. The composite film was tested by UV-visible spectrophotometer equipped with an integrating sphere, and the transmittance of visible light was 76%, and the transmittance of ultraviolet light was 38%.

[0081] Example 6

[0082] A method for preparing a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet light, comprising the following steps:

[0083] ① Lignin and tannin extraction: Lignin and tannin were extracted separately by solvothermal method. The extraction conditions of lignin were as follows: 9 g pine wood powder, 300 mL mixed solvent (210 mL acetone and 90 mL secondary water), extraction temperature 220°C, time 2 h, followed by extraction with dichloromethane, collecting the organic phase, removing the organic solvent by rotary evaporation, and drying in an oven at 105°C to obtain the organic-soluble lignin, with a yield of 27.2%; the extraction conditions of tannin were as follows: 50 g black wattle bark powder, 500 mL mixed solvent (350 mL acetone and 150 mL secondary water), extraction temperature 60°C, time 3 h, followed by removal of the organic solvent by rotary evaporation, and water-insoluble black wattle bark tannin was obtained after centrifugal washing, with a yield of 1.6%.

[0084] ② Preparation of lignin-tannin composite nanoparticles: Add 240 mg of lignin and 160 mg of black wattle bark tannin to 80 mL of mixed solvent (56 mL of acetone and 24 mL of distilled water), stir with a glass rod to dissolve them completely, and place them in an ultrasonic environment. The ultrasonic conditions are: 30°C, 45 kHz, 100%. 480 mL of distilled water is added dropwise at a flow rate of 5 mL / min through a constant flow pump. After the addition is completed, continue to ultrasonicate for 30 minutes to allow lignin and tannin to fully self-assemble. Centrifuge, remove the supernatant, continue to centrifuge and wash with water 3 times, and freeze-dry to obtain lignin-black wattle bark tannin composite nanoparticles with a yield of 54.9%.

[0085] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃ for 2h, dissolve PVA completely to obtain PVA solution; add the above-prepared lignin-tannin composite nanoparticles to the PVA solution at an addition amount of 2%, stir magnetically, at 60℃ for 0.5h, mix PVA and lignin-tannin composite nanoparticles thoroughly, pour into 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould to obtain composite film, store in a desiccator, the composition of the composite film is PVA-LT. The composite film was tested by UV-visible spectrophotometer equipped with an integrating sphere, and the transmittance of visible light was 64%, and the transmittance of ultraviolet light was 26%.

[0086] Example 7

[0087] A method for preparing a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet light, comprising the following steps:

[0088] ① Lignin and tannin extraction: Lignin and tannin were extracted separately by solvothermal method. The extraction conditions of lignin were as follows: 3 g pine wood powder, 300 mL mixed solvent (210 mL acetone and 90 mL secondary water), extraction temperature 200 ° C, time 2 h, followed by extraction with dichloromethane, collecting the organic phase, removing the organic solvent by rotary evaporation, and drying in an oven at 105 ° C to obtain the organic-soluble lignin, with a yield of 25.6%; the extraction conditions of tannin were as follows: 50 g Acacia mangium bark powder, 500 mL mixed solvent (350 mL acetone and 150 mL secondary water), extraction temperature 50 ° C, time 3 h, followed by removal of the organic solvent by rotary evaporation, and water-insoluble Acacia mangium tannin was obtained after centrifugal washing, with a yield of 2.0%.

[0089] ② Preparation of lignin-tannin composite nanoparticles: 160 mg of lignin and 240 mg of Acacia mangium tannin were added to 16 mL of mixed solvent (11.2 mL of acetone and 4.8 mL of distilled water), stirred with a glass rod to completely dissolve them, and placed in an ultrasonic environment. The ultrasonic conditions were: 30°C, 45 kHz, 100%. 96 mL of distilled water was added dropwise at a flow rate of 2 mL / min through a constant flow pump. After the addition was completed, ultrasound was continued for 30 minutes to allow lignin and tannin to fully self-assemble. The mixture was centrifuged, the supernatant was removed, and centrifugation and water washing were continued for 3 times. The mixture was freeze-dried to obtain lignin-Acacia mangium tannin composite nanoparticles with a yield of 61.9%.

[0090] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃ for 2h, dissolve PVA completely to obtain PVA solution; add the above-prepared lignin-tannin composite nanoparticles to the PVA solution at an addition amount of 6%, stir magnetically, at 60℃ for 0.5h, mix PVA and lignin-tannin composite nanoparticles thoroughly, pour into 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould to obtain composite film, store in a desiccator, the composition of the composite film is PVA-LT. The composite film was tested by a UV-visible spectrophotometer equipped with an integrating sphere, and the transmittance of visible light was 41% and the transmittance of ultraviolet light was 19%.

[0091] Example 8

[0092] A method for preparing a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet light, comprising the following steps:

[0093] ① Lignin and tannin extraction: Lignin and tannin were extracted separately by solvothermal method. The extraction conditions of lignin were as follows: 18 g pine powder, 300 mL mixed solvent (210 mL acetone and 90 mL secondary water), extraction temperature 220°C, time 2 h, followed by extraction with dichloromethane, collecting the organic phase, removing the organic solvent by rotary evaporation, and drying in an oven at 105°C to obtain the organic-soluble lignin, with a yield of 26.5%; the extraction conditions of tannin were as follows: 50 g larch bark powder, 500 mL mixed solvent (350 mL acetone and 150 mL secondary water), extraction temperature 50°C, time 3 h, followed by removal of the organic solvent by rotary evaporation, and water-insoluble larch tannin was obtained after centrifugal washing, with a yield of 5.8%.

[0094] ② Preparation of lignin-tannin composite nanoparticles: Add 200 mg of lignin and 200 mg of larch tannin to 40 mL of mixed solvent (28 mL of acetone and 12 mL of distilled water), stir with a glass rod to dissolve them completely, and place them in an ultrasonic environment. The ultrasonic conditions are: 30°C, 45 kHz, 100%. 240 mL of distilled water is added dropwise at a flow rate of 5 mL / min through a constant flow pump. After the addition is completed, continue to ultrasonicate for 30 minutes to allow lignin and tannin to fully self-assemble. Centrifuge, remove the supernatant, continue to centrifuge and wash with water 3 times, and freeze-dry to obtain lignin-larch tannin composite nanoparticles with a yield of 45.5%.

[0095] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃ for 2h, dissolve PVA completely to obtain PVA solution; add the above-prepared lignin-tannin composite nanoparticles to the PVA solution at an addition amount of 10%, stir magnetically, at 60℃ for 0.5h, mix PVA and lignin-tannin composite nanoparticles thoroughly, pour into 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould to obtain composite film, store in a desiccator, the composition of the composite film is PVA-LT. The composite film was tested by a UV-visible spectrophotometer equipped with an integrating sphere, and the transmittance of visible light was 23%, and the transmittance of ultraviolet light was 1%.

[0096] Example 9

[0097] A method for preparing a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet light, comprising the following steps:

[0098] ① Lignin and tannin extraction: Lignin and tannin were extracted separately by solvothermal method. The extraction conditions of lignin were as follows: 18 g pine powder, 300 mL mixed solvent (210 mL acetone and 90 mL secondary water), extraction temperature 200 ° C, time 2 h, followed by extraction with dichloromethane, collecting the organic phase, removing the organic solvent by rotary evaporation, and drying in an oven at 105 ° C to obtain the organic-soluble lignin, with a yield of 24.3%; the extraction conditions of tannin were as follows: 50 g bayberry bark powder, 500 mL mixed solvent (350 mL acetone and 150 mL secondary water), extraction temperature 60 ° C, time 3 h, followed by removal of the organic solvent by rotary evaporation, and water-insoluble bayberry tannin was obtained after centrifugal washing, with a yield of 9.4%.

[0099] ② Preparation of lignin-tannin composite nanoparticles: Add 100 mg of lignin and 300 mg of bayberry tannin to 80 mL of mixed solvent (56 mL of acetone and 24 mL of distilled water), stir with a glass rod to dissolve them completely, and place them in an ultrasonic environment. The ultrasonic conditions are: 30°C, 45 kHz, 100%. 480 mL of distilled water is added dropwise at a flow rate of 10 mL / min through a constant flow pump. After the addition is completed, continue to ultrasonicate for 30 minutes to allow lignin and tannin to fully self-assemble. Centrifuge, remove the supernatant, continue to centrifuge and wash with water 3 times, and freeze-dry to obtain lignin-bayberry tannin composite nanoparticles with a yield of 43.7%.

[0100] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃ for 2h, dissolve PVA completely to obtain PVA solution; add the above-prepared lignin-tannin composite nanoparticles to the PVA solution at a dosage of 4%, stir magnetically, at 60℃ for 0.5h, mix PVA and lignin-tannin composite nanoparticles thoroughly, pour into 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould to obtain composite film, store in a desiccator, the composition of composite film is PVA-LT. The composite film was tested by UV-visible spectrophotometer equipped with integrating sphere, and the transmittance of visible light was 51%, and the transmittance of ultraviolet light was 13%.

[0101] Comparative Example 1

[0102] A method for preparing a biodegradable film doped with lignin nanoparticles comprises the following steps:

[0103] ① Lignin extraction: Lignin was extracted by solvothermal method. The extraction conditions of lignin were as follows: 18 g pine wood powder, 300 mL mixed solvent (210 mL acetone and 90 mL secondary water), extraction temperature 220 ° C, time 2 h, followed by extraction with dichloromethane, collecting the organic phase, and removing the organic solvent by rotary evaporation. After drying in an oven at 105 ° C, the organic dissolved lignin was obtained with a yield of 26.5%.

[0104] ② Preparation of lignin nanoparticles: Add 400 mg of lignin to 40 mL of mixed solvent (28 mL of acetone and 12 mL of distilled water), stir with a glass rod to dissolve them completely, and place them in an ultrasonic environment. The ultrasonic conditions are: 30°C, 45 kHz, 100%. 240 mL of distilled water is added dropwise at a flow rate of 10 mL / min through a constant flow pump. After the addition is completed, continue to ultrasonicate for 30 minutes to allow the lignin to fully self-assemble. Centrifuge, remove the supernatant, continue to centrifuge and wash with water 3 times, and freeze-dry to obtain lignin nanoparticles with a yield of 56.7%.

[0105] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃ for 2h, dissolve PVA completely to obtain PVA solution; add the prepared lignin nanoparticles to the PVA solution at 3%, stir magnetically, at 60℃ for 0.5h, mix PVA and lignin nanoparticles thoroughly, pour into 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould to obtain composite film, store in a desiccator, the composition of composite film is PVA-L. The composite film was tested by UV-visible spectrophotometer equipped with integrating sphere, the transmittance of visible light: 47%, the transmittance of ultraviolet light: 14%.

[0106] Comparative Example 2

[0107] A method for preparing a biodegradable film doped with tannin nanoparticles comprises the following steps:

[0108] ① Tannin extraction: Tannin was extracted by solvothermal method. The extraction conditions of tannin were as follows: 50 g bayberry bark powder, 500 mL mixed solvent (350 mL acetone and 150 mL secondary water), extraction temperature 50 ° C, time 3 h, and then the organic solvent was removed by rotary evaporation. After centrifugation and water washing, water-insoluble bayberry tannin was obtained, with a yield of 9.0%.

[0109] ② Preparation of tannin nanoparticles: Add 400 mg of bayberry tannin to 40 mL of mixed solvent (28 mL of acetone and 12 mL of distilled water), stir with a glass rod to dissolve them completely, and place it in an ultrasonic environment. The ultrasonic conditions are: 30°C, 45 kHz, 100%. Add 240 mL of distilled water at a flow rate of 10 mL / min through a constant flow pump. After the addition is completed, continue to ultrasonicate for 30 minutes to allow the tannin to fully self-assemble. Centrifuge, remove the supernatant, continue centrifugation and wash with water 3 times, and freeze-dry to obtain bayberry tannin nanoparticles with a yield of 37.4%.

[0110] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃ for 2h, dissolve PVA completely to obtain PVA solution; add the prepared bayberry tannin nanoparticles to the PVA solution at 3%, stir magnetically, at 60℃ for 0.5h, mix PVA and bayberry tannin nanoparticles thoroughly, pour into 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould to obtain composite film, store in a desiccator, the composition of composite film is PVA-T. The composite film is tested by UV-visible spectrophotometer equipped with integrating sphere, the transmittance of visible light is 83%, and the transmittance of ultraviolet light is 21%.

[0111] Comparative Example 3

[0112] A method for preparing a biodegradable film doped with tannin and lignin mixed nanoparticles comprises the following steps:

[0113] ① Lignin and tannin extraction: Lignin and tannin were extracted separately by solvothermal method. The extraction conditions of lignin were as follows: 18 g pine powder, 300 mL mixed solvent (210 mL acetone and 90 mL secondary water), extraction temperature 220°C, time 2 h, followed by extraction with dichloromethane, collecting the organic phase, removing the organic solvent by rotary evaporation, and drying in an oven at 105°C to obtain the organic-soluble lignin, with a yield of 26.5%; the extraction conditions of tannin were as follows: 50 g bayberry bark powder, 500 mL mixed solvent (350 mL acetone and 150 mL secondary water), extraction temperature 50°C, time 3 h, followed by removal of the organic solvent by rotary evaporation, and water-insoluble bayberry tannin was obtained after centrifugal washing, with a yield of 9.0%.

[0114] ② Preparation of lignin nanoparticles and tannin nanoparticles: Add 200 mg of lignin and 200 mg of bayberry tannin to 40 mL of mixed solvent (28 mL of acetone and 12 mL of distilled water), respectively, stir with a glass rod to dissolve them completely, place them in an ultrasonic environment, ultrasonic conditions: 30°C, 45 kHz, 100%, remove the supernatant, continue centrifugation and water washing 3 times, and freeze-dry to obtain the yield of lignin nanoparticles: 53.4%, and the yield of bayberry tannin nanoparticles: 34.2%.

[0115] ③ Preparation of composite film: prepare 3% PVA solution, stir magnetically, dissolve at 90℃ for 2h, dissolve PVA completely to obtain PVA solution; add lignin-tannin composite nanoparticles prepared above to PVA solution at 3%, stir magnetically, at 60℃ for 0.5h, mix PVA and lignin-tannin composite nanoparticles thoroughly, pour into 90mm polystyrene culture dish after ultrasonic degassing, dry naturally at room temperature, demould to obtain composite film, store in desiccator, the composition of composite film is PVA-(L+T). Use UV-visible spectrophotometer with integrating sphere to test composite film, visible light transmittance: 64%, UV transmittance: 17%.

[0116] Performance Testing

[0117] (1) Scan and count the lignin nanoparticles and lignin-bayberry tannin nanoparticles and their particle size distribution. Figure 1 It can be seen that the average particle size of the lignin-bayberry tannin composite nanoparticles is smaller than the average particle size of the lignin nanoparticles. The average particle size of the lignin nanoparticles is 0.47 μm, and the average particle size of the lignin-bayberry tannin composite nanoparticles is 0.25 μm.

[0118] (2) The distribution of lignin nanoparticles and lignin-tannin composite nanoparticles in PVA film was tested. Figure 2 It can be seen that the lignin nanoparticles are obviously aggregated in the film, while the lignin-tannin composite nanoparticles are evenly dispersed in the film.

[0119] (3) The UV-visible transmittance curves and UV protection index values ​​of the four composite films with different compositions in Example 1 and Comparative Examples 1-3 were tested using a UV-visible spectrophotometer equipped with an integrating sphere, with a scanning range of 200 to 800 nm, T%, a slit width of 2 nm, and a scanning interval of 1 nm.

[0120] Test results see Figure 3 ,from Figure 3 It can be seen that for tannins from different sources (including bayberry tannin, larch tannin, tangerine tannin, acacia mangium tannin and black wattle bark tannin), the UV blocking ability of the biodegradable film doped with lignin-tannin composite nanoparticles (PVA-LT) is better than that of the biodegradable film doped with single lignin nanoparticles (PVA-L), single tannin nanoparticles (PVA-T) and the biodegradable film doped with lignin and tannin mixed nanoparticles (PVA-(L+T)), while maintaining a good transmittance.

[0121] (4) A certain amount of four different photosensitive pesticides are placed in an open opaque container, and the open opaque container is covered with the biodegradable film with high light transmittance and high efficiency in shielding ultraviolet rays provided in Example 1 of the present invention, and irradiated for a set time under a 365nm ultraviolet lamp. After the four different photosensitive pesticides are redissolved in ethanol, the absorbance values ​​are measured at the maximum absorption wavelength using an ultraviolet spectrophotometer. The maximum absorption wavelengths are 254nm, 221nm, 272nm, and 249nm, respectively. The photodegradation performance of the four different photosensitive pesticides under the cover of the biodegradable film with high light transmittance and high efficiency in shielding ultraviolet rays provided in Example 1 of the present invention is tested.

[0122] Test results see Figure 4 The four representative photosensitive pesticides are the insecticide avermectin, the plant growth regulator indole-3-acetic acid, the herbicide oxyfluorfen, and the fungicide trifloxystrobin. Figure 4 It can be seen that for four representative photosensitive pesticides, the PVA film mixed with lignin-tannin composite nanoparticles can significantly extend the working life of the four representative photosensitive pesticides.

[0123] The above test results show that the UV transmittance of the lignin-tannin composite nanoparticle film (PVA-LT) prepared by the synergistic self-assembly of lignin and tannin provided by the present invention is lower than that of the single lignin nanoparticle film (PVA-L) and the single tannin nanoparticle film (PVA-T), and the visible light transmittance is higher than that of the single lignin nanoparticle film (PVA-L). It is expected to be widely used in the fields of agricultural greenhouse films and the like.

[0124] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A biodegradable film with high light transmittance and high UV shielding efficiency, characterized in that: The invention comprises a bio-based degradable film and lignin-tannin composite nanoparticles located in the bio-based degradable film.

2. The highly light-transmitting and highly efficient UV-shielding biodegradable film according to claim 1, characterized in that: The addition amount of the lignin-tannin composite nanoparticles in the bio-based degradable film is 1%-10%, preferably 3%-5%.

3. The highly light-transmitting and highly efficient UV-shielding biodegradable film according to claim 2, characterized in that: The mass ratio of the lignin to the tannin is (9:1)-(1:9), preferably (6:4)-(4:6); Preferably, the tannin includes at least one of bayberry tannin, larch tannin, tangerine tannin, acacia mangium tannin, and black wattle bark tannin; Preferably, the lignin includes at least one of organically soluble lignin, alkali lignin, enzymatically hydrolyzed lignin, and sodium lignin sulfonate.

4. The highly light-transmitting and highly efficient UV-shielding biodegradable film according to any one of claims 1 to 3, characterized in that: The bio-based degradable film is prepared by using biodegradable polymers, and the biodegradable polymers include one or more of polyvinyl alcohol, polylactic acid, chitosan, and gelatin.

5. A method for preparing a highly light-transmitting and highly efficient UV-shielding biodegradable film according to any one of claims 1 to 4, characterized in that: The method comprises: adopting a solution casting method to prepare a biodegradable film with high light transmittance and high efficiency in shielding ultraviolet rays.

6. The preparation method according to claim 5, characterized in that: The preparation of the lignin-tannin composite nanoparticles comprises: adding the lignin and the tannin into a mixed solvent of acetone and water, stirring and dissolving, and obtaining a mixed solution; placing the mixed solution in an ultrasonic environment, dripping distilled water therein, and continuing ultrasonication after the dripping is completed to allow the lignin and the tannin to fully self-assemble, thereby obtaining the lignin-tannin composite nanoparticles; Preferably, the mass ratio of the lignin to the tannin is (9:1)-(1:9), more preferably (6:4)-(4:6); Preferably, the concentration of the lignin-tannin solution is 1 mg / mL-50 mg / mL, more preferably 5 mg / mL-10 mg / mL; Preferably, the distilled water droplet acceleration is 1 mL / min-20 mL / min, more preferably 5 mL / min-10 mL / min; Preferably, the method further comprises: after the lignin and the tannin are fully self-assembled, centrifuging the crude product, removing the supernatant, continuing to centrifuge and wash, and then freeze-drying to obtain the lignin-tannin composite nanoparticles.

7. The preparation method according to claim 6, characterized in that: The preparation of lignin comprises: extracting lignin from a first biomass raw material by a solvent thermal method, and extracting it with dichloromethane to obtain organically dissolved lignin; Preferably, the temperature for extracting lignin from the first biomass raw material by solvothermal method is 180°C-240°C, more preferably 200°C-220°C; Preferably, the solid-liquid ratio of the lignin in the first biomass raw material extracted by the solvothermal method is (1:100)-(10:100), more preferably (3:100)-(6:100); Preferably, the ratio of acetone to water in extracting lignin from the first biomass raw material by solvothermal method is (1:9)-(9:1), more preferably (4:6)-(9:1); Preferably, the extraction time of lignin in the first biomass raw material by the solvothermal method is 0.5h-3h, more preferably 1h-2h; Preferably, the first biomass raw material includes at least one of pine wood powder and red cedar powder; Preferably, the first biomass raw material is placed in a mixed solvent of acetone and water and kept at 180°C-240°C for a period of time, and then the obtained extract is extracted with dichloromethane, and the extracted organic phase is subjected to rotary evaporation to remove dichloromethane and acetone, and then dried to obtain organic dissolved lignin.

8. The preparation method according to claim 6, characterized in that: The preparation of the tannin comprises: extracting tannin from the second biomass raw material by a solvent thermal method, and obtaining water-insoluble tannin by distilled water precipitation; Preferably, the temperature for extracting tannin from the second biomass raw material by solvothermal method is 40°C-80°C, more preferably 50°C-60°C; Preferably, the solid-liquid ratio of the tannin extracted from the second biomass raw material by the solvothermal method is (1:100)-(20:100), more preferably (5:100)-(15:100); Preferably, the ratio of acetone to water for extracting tannins from the second biomass raw material by solvothermal method is (1:9)-(9:1), more preferably (4:6)-(9:1); Preferably, the extraction time of tannin in the second biomass raw material by solvothermal method is 0.5h-6h, more preferably 2h-4h; Preferably, the second biomass raw material includes at least one of waxberry, larch, mandarin orange, acacia mangium, and black wattle bark; Preferably, the second biomass raw material is placed in a mixed solvent of acetone and water, kept at 40°C-80°C for a period of time, and then the obtained extract is subjected to rotary evaporation to remove acetone, centrifuged and washed with water, and then dried to obtain water-insoluble tannins.

9. The preparation method according to claim 5, characterized in that: The preparation of the highly light-transmitting and highly efficient UV-shielding biodegradable film comprises: mixing the lignin-tannin composite nanoparticles with a biodegradable polymer solution, and then forming a film by a solution casting method to obtain a highly light-transmitting and highly efficient UV-shielding biodegradable film; Preferably, the addition amount of the lignin-tannin composite nanoparticles is 1%-10%, more preferably 3%-5%; Preferably, the mass concentration of the biodegradable polymer solution is 3% and the dissolution temperature is 90°C; Preferably, the biodegradable polymer includes one or more of polyvinyl alcohol, polylactic acid, chitosan and gelatin.

10. Use of the highly light-transmitting and highly efficient UV-shielding biodegradable film according to any one of claims 1 to 4 in agricultural greenhouse films.

Citation Information

Patent Citations

  • Full-biodegradable PVA (polyvinyl alcohol) composite film with strong toughness and good antibacterial property and preparation method thereof

    CN116444833A

  • Preparation method of walnut shell lignin enhanced polyvinyl alcohol food preservative film

    CN118580533A

  • Method for manufacturing ultraviolet ray- and high-energy blue light-blocking film comprising lignin-derived carbon quantum dots

    WO2024111815A1

Cited By

  • Lignin fiber composite material and preparation method thereof

    CN120554859A